(3GdHWGdI hOhQ Gdhba hGdRcGI aj ehGLgJgGs (3OQGSI ebGQfIs - (3eZGRj(B, (3eMeO YHO Gddgs ((3GdGScfOQjIs (3OGQ GdLGeYI GdLOjOIs, 2005)
(3eaghe GdHWGdI hCTHGQgG hehba GdTQjYI GdGSdGejI efgG(B: (3eaghe GdHWGdI hCSHGHgG ebGQfI HGdTQjYI GdGSdGejI, BKGQ GdHWGdI Ydi GdfGMjI GdGOGQjI eY HjGf ehba GdTQjYI GdGSdGejI, BKGQ GdHWGdI Ydi GdfGMjI GdGOGQjI, ehba GdTQjYI GdGSdGejI ef gPg GdBKGQ, BKGQ GdHWGdI Ydi GdfGMjI GdGLJeGYjI eY HjGf ehba GdTQjYI GdGSdGejI, BKGQ GdHWGdI Ydi GdfGMjI GdGLJeGYjI, ehba GdTQjYI GdGSdGejI ef gPg GdCKGQ, BKGQ GdHWGdI Ydi GdfGMjI GdGbJUGOjI eY HjGf ehba GdTQjYI GdGSdGejI, BKGQ GdHWGdI ef GdfGMjI GdGbJUGOjI, ehba GdTQjYI GdGSdGejI ef gPg GdBKGQ, BKGQ GdHWGdI Ydi GdfGMjI GdSjGSjI eY HjGf ehba GdTQjYI GdGSdGejI, OhQ Gdhba ef ehGLgI GdHWGdI, OhQ GdRcGI aj ehGLgI GdHWGdI(B.s
Keywords: (3GdHWGdIs; (3GdRcGI(B- (3GdLhGfH GdGbJUGOjIs; (3Gdhba(B- (3GdLhGfH GdGbJUGOjIs